Digital signal processing and applications - Stranneby, Dag (Elsevier/Newnes, 2004)
A uniquely practical DSP text, this book gives a thorough understanding of the principles and applications of DSP with a minimum of mathematics, and provides the reader with an introduction to DSP applications in telecoms, control engineering and measurement and data analysis systems. The new edition contains: Expanded coverage of the basic concepts to aid understanding New sections on filter sysnthesis, control theory and contemporary topics of speech and image recognition Full solutions to all questions and exercises in the book A complete on-line resource The on-line resource offers instructors and students complete lecture notes, lecture videos, PowerPoint slides for presentations, final exams and solutions, project exercises, URLs to DSP applet experiment animations and e-meeting software for direct communication with the authors. Assuming the reader already has some prior knowledge of signal theory, this textbook will be highly suitable for undergraduate and postgraduate students in electrical and electronic engineering taking introductory and advanced courses in DSP, as well as courses in communications and control systems engineering. It will also prove an invaluable introduction to DSP and its applications for the professional engineer. Expanded coverage of the basic concepts to aid understanding, along with a wide range of DSP applications New textbook features included throughout, including learning objectives, summary sections, exercises and worked examples to increase accessibility of the text Full solutions to all questions and exercises included in the book, with extra resources on-line.